Earnings Management in the Private Equity Divestment Process on Warsaw Stock Exchange - Tomasz Sosnowski (Institute of Economic Research (IER), 2017)
Prior studies suggest that companies which go public manage earnings in order to inflate the issue price. However, for PE funds the use of such activity can be costly in terms of the reputation capital as they are repetitive stock market players. The main aim of the study is to empirically investigate the use of pre-IPO earnings management by private equity funds in the process of divestment conducted on a stock exchange. I provide comparisons between PE-backed companies and firms with a similar initial market value and growth potential, using the method of single-linkage clustering to build the study sample. In order to assess the pre-IPO earnings management I apply the discretionary accruals model of Larcker and Richardson [2004]. I do not find evidence that the presence of PE fund among the shareholders of the company in the period preceding first listing of shares on a stock market constrains the use of earnings management prior to the IPO. The difference between the discretionary accruals in PE-backed and matched companies, when controlling for the market value and book-to-market ratio, is statistically insignificant.
Keywords: G24; G32; G34; 330; Initial public offering; IPO; Private equity; Earnings management